Bond Ratings dan Antesedennya: Studi Empiris di Bursa Efek Indonesia - Wendy, Wendy; Sianturi, Rosita Naomi (Fakultas Ekonomi dan Bisnis, UNTAN, 2017)
This paper provides the empirical evidence of corporate growth, maturity, and operating cash flows on the bond ratings. It was conducted on 34 bonds issued by the 16 non-financial companies on the Indonesia Stock Exchange (IDX) which also issued bonds, registered in the Indonesia Bond Market Directory, and rated by PEFINDO during 2012 - 2014. The hypotheses were tested using the logistic regression analysis. The result shows that corporate growth has significant effect on the bond ratings, while maturity and operating cash flow have no significant effect. Another finding shows that the firm size can also affect the bond ratings.